The Impact of effective leadership on the performance of individuals in Saudi Airlines - Aljohani, Abdulrahman (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to get acquainted with the actual practices of effective leadership through the democratic style of the Saudi Airlines Company and to know the reality of the level of performance from their point of view of the Saudi Airlines Company, as well as to develop a proposed model to show the most important variables that affect raising the level of individuals ’performance according to effective leadership practices through the democratic pattern in Leadership at Saudi Airlines Company, the study relies on the descriptive and analytical approach to clarify its objectives, and to identify the extent of practicing effective leadership aspects by following the democratic management in the Saudi Arabian Airlines Company and its role in the performance of individuals. As this approach helps to study the reality, diagnose, express and describe the phenomenon under study accurately. The study population consists of all employees and employees working for the Saudi Airlines Company in the Jeddah branch (central) and their number reached 1497, and the target sample size was determined by 100 individuals, and the link to the questionnaire was distributed to them. The responses valid for statistical analysis reached 84 individuals, i.e. 84% of the target. According to the results, the study made several recommendations, the most important of which is raising the level of individuals' awareness of some democratic leadership practices and increasing human and social communication with subordinates as this contributes to raising performance efficiency.
Keywords: Impact; Effective Leadership; Performance; Employees; Saudi Airlines